Emotion regulation in social anxiety and depression: a systematic review of expressive suppression and cognitive reappraisal - Dryman, M. Taylor; Heimberg, Richard G. (Clinical psychology review, 2018)
Social anxiety disorder (SAD) and major depressive disorder (MDD) are highly comorbid, and together they result in greater functional impairment and a poorer prognosis than either condition alone. Theoretical models implicate impairments in emotion regulation in the development and maintenance of internalizing disorders, yet there has been no systematic comparison of emotion regulation in social anxiety and depression. The current review presents an in-depth examination of the literature on two widely-studied emotion regulation strategies, expressive suppression (ES) and cognitive reappraisal (CR), in SAD and MDD. Our review indicated that SAD is broadly characterized by an overreliance on ES, which is associated with negative social and emotional consequences. SAD is also characterized by ineffective utilization of CR, which inhibits the potential positive emotional benefits of this adaptive emotion regulation strategy. In contrast, MDD is broadly characterized by an underutilization of CR, which may be particularly detrimental in stressful or uncontrollable situations. For both SAD and MDD, treatment intervention appears to address deficits in CR but not ES. After reviewing the literature, we propose multiple pathways by which impairments in ES and CR may increase risk for the co-occurrence of SAD and MDD. Clinical implications and future research directions are also discussed. •Social anxiety is characterized by an overreliance on expressive suppression.•Social anxiety is also connected to ineffective use of cognitive reappraisal.•Evidence is mixed regarding the role of expressive suppression in depression.•Depression is strongly associated with an underutilization of cognitive reappraisal.•Emotion regulation may play a role in co-occurring social anxiety and depression.